FACTORS INFLUENCING REGIONAL FINANCIAL MANAGEMENT AT THE EDUCATION, YOUTH AND SPORTS OFFICE OF POLEWALI MANDAR - ismayanti2, ismayanti2 (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2022)
This study aims to determine the effect of regulations, commitments, and characteristics, supporting devices on regional financial management at the Education, Youth, and Sports Office of Polewali Mandar Regency. Data was collected through documentation, observation, and questionnaires. The sample of teachers is 38 respondents. Data processing consists of description analysis, correlation analysis, and regression analysis. The results of this study are (1) based on the results of testing using the coefficients test (T-test), the coefficient value between regulatory variables and commitment to regional financial management is 0.007 <0.05. These results indicate that there is a positive and significant relationship between regulation and commitment variables with local financial management at a significance of 0.05 or 5%; (2) based on the test results using the coefficients test (T-test), the coefficient value between the characteristic variables and the supporting tools for regional financial management is 0.001 < 0.05. These results indicate that there is a positive and significant relationship between the characteristics and supporting instruments variables with local financial management at a significance of 0.05 or 5%; (3) based on the ANOVA regression test (F test), the coefficient value between regulation, commitment, and characteristics, supporting devices for regional financial management is 0.00 < 0.05. These results indicate that there is a positive and significant relationship between regulation, commitment, and characteristics, supporting tools for regional financial management at a significance of 0.05 or 5%